Management of Project-Based Learning Model at Sekolah Alam Junior High School - Masduki Ahmad (AL-ISHLAH: Jurnal Pendidikan, 2021)
The purpose of this research is to learn more about how project-based learning models are planned, implemented, and evaluated at Sekolah Alam Cikeas Junior High School. This study employed a descriptive method and a qualitative approach. Observation, interviews, and documentation studies were used to gather data. This research shows thatthe management of project-based learning environmental education programs is carried out by the Sekolah Alam Cikeas Junior High School very well.The quality of the learning implementation has exceeded the quality of the implementation of environmentally sound learning when compared to other schools. The implementation of Project-Based Learning at Sekolah Alam Cikeas Junior High School, which focuses on character and moral development, will produce students who can compete in academics and overall quality.Management that has been done in an organised manner makes Project Based Learning implemented in a more measured manner and produces output as expected without wasting existing resources.